1998
DOI: 10.1128/jb.180.4.979-984.1998
|View full text |Cite
|
Sign up to set email alerts
|

New Flagellin-Specifying Genes in Some Escherichia coli Strains

Abstract: Data for further development of the flagellar antigen genetics of the species Escherichia coli are reported. Two new flagellin genes named fllA and flmA were found in E. coli 781-55, E2987-73, and E223-69, the test strains for E. coli flagellar antigens H44, H55, and H54, respectively (collection of the International Escherichiaand Klebsiella Centre of the World Health Organization, Copenhagen, Denmark). Two alleles of fllAwere identified that encode flagellar antigens H44 (fllA 44) and H55 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…4). Others were randomly assembled into eight reaction 5 kits. In multiple PCR assays, the same results as those for simplex PCR assays were obtained from all reference strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Others were randomly assembled into eight reaction 5 kits. In multiple PCR assays, the same results as those for simplex PCR assays were obtained from all reference strains.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, flagellin is encoded by the fliC gene on the chromosomal locus or its homologues (non-fliC flagellin-coding genes) at loci other than fliC, such as flkA, fllA, and flmA (4)(5)(6)(7)(8). When a mobile element carrying non-fliC and its attendant gene is inserted in the chromosome, these genes may mediate reversible flagellar phase variation.…”
mentioning
confidence: 99%
“…In total, 139 (74%) isolates were motile in soft agar, of which 25 (18%) isolates showed no amplification of the fliC gene. This could be due to sequence variations in fliC among different E. coli isolates (40) and/or the expression of another or new flagellin genes (41). Although Pratt and Kolter found that motility, and not chemotaxis, is required for E. coli to form a biofilm (21), it is also possible for nonmotile strains to adhere to surfaces and develop a biofilm (42).…”
Section: Discussionmentioning
confidence: 99%
“…PCR detection of fliC alleles has been used for molecular H-typing for some time (Wang et al ., 2003). However, some E. coli isolates have an alternative flagellar phase, due to the presence of an additional flagellin gene (flnaA, fllA, fmlA or flkA) , similar to those found in Salmonella species (Feng et al ., 2008; Ratiner, 1998; Ratiner et al ., 2010; Tominaga, 2004; Tominaga & Kutsukake, 2007).…”
Section: Introductionmentioning
confidence: 99%